Studies on the epidemiology of neurotropic viruses in Sarawak : 1998 to 2003 - Yuwana, Podin (Universiti Malaysia Sarawak, (UNIMAS), 2005)
HFMD and infection of the CNS were recognized as important diseases to be studied in Sarawak due to the serious health implications they pose. Following the realization, two surveillance programmes were set up in 1998 to monitor these diseases in Sarawak. This study reports the findings of a six-year observation from 1998 to 2003 of the two surveillance programmes, including a case-finding study in Bintulu during an outbreak of HFMD in 2000. HEV71-related HFMD outbreaks were found to occur in three-year interval.